Nutritional Status and Its Association with Cognitive Function among School Aged Children at Soddo Town and Soddo Zuriya District, Southern Ethiopia: Institution Based Comparative Study - Tesfaye Honja Kabero; Tafese Bosha; Fentaw Wassie Feleke; Demewoz Haile Weldegebreal; Barbara Stoecker (SAGE Publishing, 2021)
About 1 billion stunted school-aged children are growing up with impaired mental development which can lead to low cognitive performance, reduced school achievement, and low productivity. But there is scarce evidence on cognitive function, school performance and their associated factors among school aged children. The main aim of this study was to assess cognitive function, school performance and determine their association with nutritional status among school children aged 7 to 10 years at Soddo Town and Soddo Zuriya Woreda, Wolaita Zone, Southern Ethiopia. Institutional comparative cross-sectional study was conducted on a total sample of 178 primary school children. The Raven's Color Progressive Matrices (RCPM) and selected tests from Kaufman assessment battery for children second edition were used. Mid-year average students' examination result was also used. Data were analyzed by using SPSS version 25, WHO Anthro plus, and independent sample t -test. Bivariate and multivariate linear regression analyses were also used. Mean (±SD) cognitive test scores of urban study participants was 18.7 ± 3.4 for RCPM which was higher ( P  < .001) as compared to rural (16.5 ± 3.3). The urban mean cognitive test scores was also higher for both pattern reasoning and visual processing with ( P  < .001) as compared to rural counterparts. School performance was higher ( P  < .001) for urban. Maternal education ( P  < .002) and wealth index ( P  < .006) were positively predicted while stunting ( P  < .001) negatively predicted cognitive function test scores and school performance. Cognitive function and school performance of study participants were associated with their nutritional status and rural participants had significantly lower mean scores as compared to urban counterparts. Further study should be done to community level.